Calculation of fatigue life for multiple track railway bridges. (20th May 2009) - O'Dwyer, D.W.; Gallagher, R.P.
This paper considers the fatigue analysis of both single-track and multi-track railway bridges. The paper presents an algorithm for fatigue assessment of single track bridges that uses superposition to construct the stress history for a train using the stress history for a single moving load. The traditional damage calculation algorithms used in current fatigue codes are introduced and the limitations of the widely-used Palmgren-Miner hypothesis are identified. The paper highlights the difficulty of assessing the fatigue damage due to simultaneous loading of multiple tracks in multi-track bridges and presents algorithms for calculating the fatigue damage experienced by multi-track bridges. The method presented is based on the Palmgren-Miner damage hypothesis. The use of random arrival and random delay models is discussed and the problems associated with these assumptions, and the corresponding advantages of experimental measurements, are highlighted. Field measurements are considered but the emphasis of the paper is on the development of probabilistic techniques. The paper also considers the particular case of twin-track bridge elements, where the passage of a train, or axle, causes a single stress-cycle.